TATA KELOLA PEMERINTAHAN PADA SEKTOR INFORMAL (STUDI PEDAGANG KAKI LIMA DI KABUPATEN NGAWI) - Novita Trisniawan; Teguh Yuwono; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
The presence of informal sector, particularly street vendors (PKL), is an unavoidable economic reality happening to nearly all regions in Indonesia that needs special attention. On one side, street vendors have brought problems related to urban planning, social, health domain and so forth. While on the other side, street vendors are highly needed by the community in terms of fulfilling their needs and reducing the government’s burden. If managed properly, street vendors are able to provide economic improvement and community welfare in a region. Ngawi Regency is one region area inseparable from the presence of street vendors. Such informal sector has dominated centers of crowd in Ngawi Regency, including Ngawi Regional Square. Street vendors in Ngawi Regency also have also led to many problems, such as disruption to the city’s immaculacy and congestion. This research is thereby aimed to more deeply examine the Informal Sector Governance in Ngawi Regency.The present research was conducted using combination method or combining the qualitative and quantitative research with the use of observation data, interview, documentation and questionnaire in order to explain the real situation in details while using triangulation of data source, method and theory.Based on the research performed, the results obtained are: the condition and presence of street vendors in Ngawi Regency are already in accordance with the theory and concept of Informal Sector; and Ngawi Regency Government has a policy plan to relocate street vendors. Legalistic approach employed to manage street vendors is yet accurate, based on findings in the field. A combination of empowerment, structuralist and legalistic approaches is recommended in the management of street vendors.Keywords: Street Vendors, Policy, Governance Approach